Radiologic Evaluation of Bone Loss at Implants with Biocide Coated Titanium Abutments: A Study in the Dog - López-Píriz, Roberto (Public Library of Science, 2012)
The objective of the present study is to evaluate bone loss at implant abutments coated with a soda-lime glass containing silver nanoparticles subjected to experimental peri-implantitis. Five beagle dogs were used in the experiments, 3 implants were installed in each quadrant of the mandibles. Glass/n-Ag coted abutments were connected to implant platform. Cotton floss ligatures were placed in a submarginal position around the abutment necks and the animals were subject to a diet which allowed plaque accumulation, and after 15 weeks the dogs were sacrificed. Radiographs of all implant sites were obtained at the beginning and at the end of the experimentally induced peri-implantitis. The radiographic examination indicated that significant amounts of additional bone loss occurred in implants without biocide coating, considering both absolute and relative values of bone loss. Percentages of additional bone loss observed in implants dressed with a biocide coated abutment were about 3 times lower (p<0.006 distal aspect; and p<0.031 at mesial aspect) than the control ones. Within the limits of the present study it seems promising the use of soda-lime glass/nAg coatings on abutments to prevent peri-implant diseases.